1992
DOI: 10.1044/1058-0360.0103.54
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Stuttering

Abstract: A nationwide survey of pediatricians was conducted to assess their practices with and attitudes and beliefs about young children who stutter and their stuttering. Data obtained from 439 respondents were analyzed. The findings indicated mixed trends. Although the opinions of the majority of the pediatricians agreed with current information about stuttering, on several important matters a significant percentage held outdated or erroneous beliefs about the etiology of the disorder or characteristics of young chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
107
1
8

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(119 citation statements)
references
References 20 publications
3
107
1
8
Order By: Relevance
“…8 This rate was higher than previously reported, [9][10][11] presumably because our study began in infancy before speech development, and we identified many early cases missed by other studies that did not assess children until they were 3 years of age or older. 9 Although many antecedents and risk factors for stuttering have been proposed, [11][12][13][14] we did not find early stuttering onset to be associated with any social or environmental factors. Only 3.7% of the variation in stuttering onset was explained in our multivariable models.…”
contrasting
confidence: 53%
See 4 more Smart Citations
“…8 This rate was higher than previously reported, [9][10][11] presumably because our study began in infancy before speech development, and we identified many early cases missed by other studies that did not assess children until they were 3 years of age or older. 9 Although many antecedents and risk factors for stuttering have been proposed, [11][12][13][14] we did not find early stuttering onset to be associated with any social or environmental factors. Only 3.7% of the variation in stuttering onset was explained in our multivariable models.…”
contrasting
confidence: 53%
“…onset, at just 6.3%, was in line with the 9% 12-month recovery rates previously reported in the Illinois study. 11 The study also has limitations. Some cases may have been missed because parents opted out of the study at earlier waves, were lost to follow-up, or overlooked the stuttering (eg, if it was mild or if they had another child who had recovered from stuttering).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations